IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA STUDI KASUS PENDIDIKAN DI DESA YARO KECAMATAN TOBELO TIMUR KABUPATEN HALMAHERA UTARA - SIMANGE, STELLA; ROMPAS, WELSON; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : Facing globalization current and also growth of technology and science can be drawn up to the makeupof the quality of human resource. One of make-up of the quality of human resource education. Education ofvital importance to as school age child, in a condition existing environment many cause factor of problem of thathappened environment hence understanding him there must be so that is not imbued with factors. Efficacy of schoolage child depended from ourselves old fellow, governmental countryside even society only assisting, instructing tous as school age child can become good fellow. Intention of this research is to know implementation policy ofgovernment in improving the quality of human resource. this research is to give input to countryside society of yaroDistrict Of Tobelo East Sub-Province of Halmahera North more focus education quality of countryside resource ofyaro can expand. Method the used method, qualitative with descriptive approach type and also research locationcountryside of yaro District Of Tobelo East Sub-Province of Halmahera North data collecting taken circumstantialinterview and observation to informan.Pursuant to result of research there are some serious factor to improve; repairing where condition of existingenvironment still not yet fully support the quality of human resource because lack of communications andunderstanding between organization affect to society become resistance to education.Keyword : improving the quality of human resource education